Acquisition of heuristic knowledge for the prediction of the frictional behavior of surface structures created by self-excited tool vibrations - Breitsprecher, Thilo; Hense, R.; Hauer, Franz; Wartzack, Sandro; Biermann, Dirk; Willner, Kai (Key Engineering Materials, 2012)
The selective control of the frictional behavior (tailored friction) in metal forming processes is of high importance with regard to technical and economic aspects. This applies especially for the sheet-bulk-metal forming process. Milling with intentionally invoked regenerative tool vibrations can be applied in order to generate structured surfaces with tailored friction properties on the forming tool. These structures affect the formation of lubrication pockets during the forming process which determine the local frictional properties exceedingly. The full potential of this emerging technology can, however, only be revealed if the heuristic and design-relevant knowledge is acquired and provided to the tool-designer already in the early phases of process development. One thing the tool-designer has to specify is the local frictional behavior on the tool surface. But, however, he does not know which milling parameters lead to the necessary surface structures because in most cases he has no expert knowledge in milling, tribology and forming tools. In this paper data mining is used to determine the frictional behavior based on these parameters. The potential of this method in the described context is revealed by the application on data derived from simulation results, both from milling simulations and contact simulations. The latter are performed by using a Halfspace model for rough surface contact. Both approaches for these simulations, the data mining process and the results are explained to the reader.© (2012) Trans Tech Publications.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-KLMEFK.acquis
Keywords: Data mining; Halfspace model; Milling with vibrations; Self-learning system

Development of a Constitutive Friction Law based on the Frictional Interaction of Rough Surfaces - Beyer, Florian; Hauer, Franz; Willner, Kai (Tribology in Industry, 2015)
Friction has a considerable impact in metal forming. This is in particular true for sheet-bulk metal-forming (SBMF) in which local highly varying contact loads occur. A constitutive friction law suited to the needs of SBMF is necessary, if numerical investigations in SBMF are performed. The identification of the friction due to adhesion and ploughing is carried out with an elasto-plastic half-space model. The normal contact is verified for a broad range of normal loads. In addition, the model is used for the characterization of the occurring shear stress. Ploughing is determined by the work which is necessary to plastically deform the surface asperities of the new area that gets into contact during sliding. Furthermore, the surface patches of common half-space models are aligned orthogonally to the direction in which the surfaces approach when normal contact occurs. For a better reflection of the original surfaces, the element patches become inclined. This leads to a geometric share of lateral forces which also contribute to friction. Based on these effects, a friction law is derived which is able to predict the contact conditions especially for SBMF.
Keywords: half-space; elasto-plastic contact; simulation; constitutive friction law; sheet-bulk metal forming

Development of a friction law respecting plastic surface smoothing - Hauer, Franz; Willner, Kai (Key Engineering Materials, 2013)
Friction has a significant effect on the metal forming. This is in particular true for the emerging sheet-bulk metal forming process. Therefore an adequate friction law is necessary for the accurate Finite-Element modelling of the process. This friction law has to incorporate a smooth transition from the Coulomb friction law for low contact pressures to a Tresca friction law for high contact pressures. Furthermore the plastic smoothing of surface roughness has to be taken into account. A friction law fulfilling these requirements is developed based on the results of an elastic-plastic halfspace contact model. This model is verified and calibrated experimentally. Its ability to model the changes in the roughness parameters as well as the Abbott curves in normal contact is demonstrated. Copyright © 2013 Trans Tech Publications Ltd.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.develo
Keywords: Contact; Friction; Halfspace; Sheet-bulk metal forming; Simulation

Elastic-plastic halfspace simulation - Hauer, Franz; Willner, Kai (PAMM 2011, 2011)
Due to the roughness of technical surfaces only the surface peaks are in   contact for moderate contact pressures. Thus, the real contact area is smaller than the apparent contact area. Contact forces can only occur in the real contact area. Consequently it is necessary to determine the deformation of surface  asperities in order to analyse the tribological properties of surfaces. The real  contact area is usually small in initial contact. This leads to large contact  pressures which in turn lead to the plastic deformation of surface roughness  peaks. Therefore an elastic-plastic model is necessary. The halfspace model  seems to be beneficial because there is only a system of equations on a surface mesh to be solved and not on a volume mesh like in the Finite-Element-Method. This leads to a much smaller system of equations which should allow  reasonable calculation times even for large contact surfaces.
UnivIS-Import:2015-07-08:Pub.2011.tech.FT.FT-TM.elasti_5

Halfspace modeling of elastic-plastic contact of rough surfaces - Hauer, Franz; Willner, Kai (COMPLAS XI, 2011)
Friction has a significant influence on the tool lifetime and the quality of products in manufacturing processes. Real surfaces are always rough, so that for moderate loads contact occurs only at surface roughness peaks. Thus the real contact area A real is smaller than the apparent contact area A 0. Adhesive forces, which are an important contribution to friction, can only be transferred within A real. Consequently A real has to be determined in order to analyse the tribological behaviour of technical surfaces. The halfspace approach is used because of its advantage in numerical effort compared to the Finite-Element-Method. Due to the fact that contact pressures can be very large the plastic deformation of roughness peaks has to be taken into account. Therefore a three-dimensional plasticity algorithm is implemented into the halfspace model.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-TM.halfsp_9
Keywords: Computational plasticity; Contact; Halfspace; Metal forming

Halfspace Simulation of Rough Surface Contact in Metal Forming - Hauer, Franz; Willner, Kai (10th World Congress on Computational Mechanics, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-TM.halfsp_3

Normal contact simulation of non-Gaussian fractal surfaces - Hauer, Franz; Willner, Kai (Proceedings of the 81st Annual Meeting of the International Association of Applied Mathematics and Mechanics, 2010)
Friction forces between contact partners in dry friction are primarily caused by adhesion and ploughing. In adhesive contact, tangential loads are transferred by shear forces within the real contact area. The real contact area is usually smaller than the apparent contact area, because real surfaces are always rough and only the highest surface peaks are in contact for moderate loads. Thus the size of the real contact area is a suitable measurement for the behaviour in dry friction. The normal contact is simulated with a halfspace model. The contact surfaces are modelled numerically in order to enable the independent investigation of the influence of several surface properties, namely the fractal behaviour on small scales, non-Gaussian height distribution and anisotropy. Fractal behaviour means that asperities are covered with smaller asperities of the same shape. Surface anisotropy means that valleys and ridges are oriented in a certain direction.
UnivIS-Import:2015-04-16:Pub.2010.tech.FT.FT-TM.normal_8

Numerical simulation of friction in metal forming using a halfspace model - Hauer, Franz; Vierzigmann, Ulrich; Willner, Kai; Engel, Ulf (AIP Conf. Proc. 1536, 2011)
Sheet and bulk metal forming are widely used manufacturing methods. The industrial trend towards function integration leads to a demand for workpieces having features of both methods. The new forming technology sheet-bulk metal forming is a promising approach to manufacture workpieces with functional elements. Tribological aspects generally play an important role in metal forming processes. Especially for the formability of functional elements friction is very important. The coexistence of low and high contact pressures is characteristic of sheet-bulk metal forming and presents a challenge for the friction modelling. The surfaces of tool and workpiece are always rough so that initial contact only occurs at the asperities of surface roughness. Consequently for small and moderate loads the real contact area is smaller than the apparent contact area. Surface traction can only occur in the real contact area so that it is necessary to determine the real contact area in order to study the tribological behaviour of contact pairs. In order to get an accurate determination of the real contact area it is necessary to calculate the surface deformation in a three-dimensional model and to validate the simulation model by measurements. The halfspace approach has the significant advantage that only the surface has to be discretised while in a Finite Element Analysis the whole bulk has to be discretised. Consequently the numerical effort and thus the calculation time in the halfspace model are much lower than in FE-modelling. The numerical solution scheme based on the halfspace theory is presented in this paper. Results of the calculation of the real contact area of rough surfaces are compared to experimental data from ultrasonic inspection. Friction coefficients calculated with the halfspace model are compared to results of strip drawing tests. © 2011 American Institute of Physics.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-TM.numeri_9
Keywords: friction; halfspace model; metal forming; real contact area; Simulation; strip drawing; ultrasonic inspection